2015
DOI: 10.3402/meo.v20.28851
|View full text |Cite
|
Sign up to set email alerts
|

Peer-led problem-based learning in interprofessional education of health professions students

Abstract: Background: The role of peer teachers in interprofessional education has not been extensively studied. This study is designed to determine if peer-teacher-led problem-based seminars can influence medical and pharmacy students' perceptions of interprofessional education. Methods: Undergraduate medical and pharmacy students participated in one-hour problem-based learning seminars held over the course of 16 weeks. A caseÁcontrol study design was used to compare perceptions of interprofessional education between s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 12 publications
3
40
0
2
Order By: Relevance
“…Certainly, in this case, involving students as IPL facilitators, and training them alongside staff, has had a positive impact on the training for all participants. Furthermore, findings presented here support those presented by Lehrer et al (2015) positioning students as core drivers of nurturing and leading a culture of transformational change that embraces interprofessional learning and working.…”
Section: Insert Figure 2 Heresupporting
confidence: 84%
See 1 more Smart Citation
“…Certainly, in this case, involving students as IPL facilitators, and training them alongside staff, has had a positive impact on the training for all participants. Furthermore, findings presented here support those presented by Lehrer et al (2015) positioning students as core drivers of nurturing and leading a culture of transformational change that embraces interprofessional learning and working.…”
Section: Insert Figure 2 Heresupporting
confidence: 84%
“…The complexity of IPL facilitation highlights the need for appropriate preparation of IPL facilitators and evidence shows that the success of IPL can be undermined by using unskilled, or unprepared, facilitators (Milot, Museux & Careau, 2017;LeGros et al, 2015). However, and important to this initiative, evidence also show that involving students as facilitators can have a uniquely positive impact on the process of fostering a cultural change towards collaborative working (Lehrer et al, 2015). This is a notion also supported by Brewer, Flavell, Trede & Smith (2017) who propose that students have the potential to contribute to the necessary transformation of the workforce, possibly with the vision of joining what Kotter (2014) describes as the "volunteer army" of individuals needed for the transformational change.…”
Section: Introductionmentioning
confidence: 99%
“…Between 2012 and 2015, twelve studies were published highlighting pharmacy students' perceptions toward IPE and collaborative practice based on an IPE intervention. For the included articles focusing on students, the IPE sessions varied in their duration from ad hoc sessions (lasting between one and four hours) in the form of simulation 38,39 or interactive case based discussion 40 ; or 2 IPE case based sessions over a month 41,42 , to IPE activities spread over the semester [43][44][45] or in one study over two years 46 . Other studies was based on an IPE experiential learning experience [47][48][49] .…”
Section: Studies With Ipe Interventionmentioning
confidence: 99%
“…Although interdisciplinary professional education has distinct advantages, such as improved work culture, patient outcomes, and collaboration among providers (Fahey et al, 2008;Head et al, 2014;Lehrer et al, 2015;O'Leary et al, 2011;Reeves et al, 2008;Taplin et al, 2015), verbal feedback and comments from the post-training surveys (nursing) indicated that the knowledge questions and educational materials appeared to be targeted toward physicians and pharmacy providers. Commonalities exist among all provider groups related to pain assessment and management in patients with cancer.…”
Section: Discussionmentioning
confidence: 99%